2016
DOI: 10.5530/pj.2016.2.3
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Antioxidant Activity of Ethanol and Aqueous Extracts of Different Parts of Nyctanthes Arbor-tristis Linn.

Abstract: Background: Antioxidants play a major role in curing degenerative disease. In present time many synthetic antioxidants are commonly used but due to their toxic and carcinogenic effects, their use has been restricted. So the search for natural antioxidants is important. Studies on natural compounds is of interest due to their satisfactory health benefits with low toxicity. Objective: The antioxidant activity of ethanol and aqueous extract of shoot, seed and leaf of an important medicinal tree Nyctanthes arbor-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Antioxidants play vital roles in the management of neurodegenerative disorders by rescuing the neurons from free radical-induced oxidative damage [13,24]. Free radicals are highly reactive species which cause oxidative damage to healthy cells, leading to disease conditions such as neoplasms, diabetes mellitus and AD [2].…”
Section: Discussionmentioning
confidence: 99%
“…Antioxidants play vital roles in the management of neurodegenerative disorders by rescuing the neurons from free radical-induced oxidative damage [13,24]. Free radicals are highly reactive species which cause oxidative damage to healthy cells, leading to disease conditions such as neoplasms, diabetes mellitus and AD [2].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, betulinic acid was identified as an active antioxidant compound with an IC 50 of 18.03 µg/ml with the DPPH assay. This compound might interfere with the oxidation process by donating an electron to neutralize free radicals (Karan et al, 2019;Patel and Gokhale, 2016;Sousa et al, 2021). Other studies evaluated the antioxidant activities of different NAT flower extracts (ethanol, ethyl acetate, and water extracts) using DPPH radical scavenging, superoxide radical scavenging, lipid peroxidation, and reducing power assays.…”
Section: Antioxidant Effectmentioning
confidence: 99%
“…This finding indicated that although the extract showed a medium degree of antioxidant activity, its reducing power is weak. The difference in the antioxidant potency may be due to the solubility of antioxidant compounds in various solvents used in the extraction process (Mishra et al, 2016a;Patel and Gokhale, 2016).…”
Section: Antioxidant Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…Antioxidants, are vital substances which possess the ability to protect the body from possible harms caused by the free radical induced oxidative stress which damage the cells in our bodies. 1 A balance between free radicals and antioxidants is necessary for proper physiological function. 2 If the free radicals overwhelm the body's ability to regulate them, a condition known as oxidative stress ensues.…”
Section: Introductionmentioning
confidence: 99%